TRANSFORMASI KOMUNIKASI ORGANISASI MELALUI DIGITALISASI - Fardiansyah, Riko; Putri, Intan; Istighfarany, Annisa Ghina; Novasriady (CV. Lafadz Jaya, 2025)
Digitalization has become a major driving force in transforming organizational communication practices, including communication processes, media, and interaction patterns among organizational members. This study aims to analyze the transformation of organizational communication through digitalization and to examine its impact on communication effectiveness and organizational performance among Micro, Small, and Medium Enterprises (MSMEs) located in the 26 Ilir area of Palembang City. The research employs a qualitative approach, with data collected through in-depth interviews, participant observation, and documentation studies involving MSME actors directly engaged in digital-based organizational communication. The findings indicate that the digitalization of organizational communication among MSMEs in the 26 Ilir area of Palembang City accelerates information flow, improves work coordination, and fosters more flexible and responsive communication patterns. The use of digital communication platforms, such as instant messaging applications and social media, plays a significant role in supporting decision-making processes and expanding the scope of internal and external communication. However, this transformation also faces several challenges, including differences in digital literacy levels among MSME actors, limitations in technological infrastructure, and the potential for miscommunication due to reduced face-to-face interactions. In conclusion, the transformation of organizational communication through digitalization in MSMEs requires well-planned communication strategies, continuous capacity building of human resources, and ongoing adaptation to digital technological developments in order to enhance communication effectiveness and ensure sustainable competitiveness.